The Effect of I-McNamara Line Distance To Lips Width and Length On Class II Division 1 Malocclusion Treated by Begg Fixed Appliances - Karunia, Dyah (Ikatan Ortodontis Indonesia, 2013)
Introduction: Class II division 1 malocclusion often shows protuded face profile and abnormal estetis. Teeth retraction will be dane to decline lower face convexity which lips have estetical key. Retraction changes teeth position more palatally and will change teeth position distance to Mc Namara Line. Objective: This research was aimed to observe the effect of I-Mc Namara distance changes to lips width and lenght changes on Class II division 1 malocclusion treated by Begg Fixed appliance. Methods: The studies involved 30 lateral cephalogram of patients of 18-30 years old, malocclusion Class II division 1 by 4 first premolar extaction, and completely treated by Begg Technique. The measurement of I-Mc Namara line distance, lips width and lenght was employedon the pre and post treatment cephalograms. Statistical t analysis was applied to observe changes pre and post treatment, and Correlation analysis was used evaluate the effect of I-Mc Namara Line distance changes to lips width and lenght changes. Discusion and Result: Anterior teeth retraction by begg fixed appliance resultedlinier changes of I upper-Mc Namara Line and I lower-Mc Namara Line distance decreased after treatment (p<0.05). It also showed significantly differences in lips width and lips lenght between pre and post treatments (p<0.05). The mean width and lenght of upper and lower lips were bigger after treatment. However, there was no correlation between the change of teh I-Mc Namara Line Distance and changes of lips width and lenght (p>0.05). Conclusion: There was encreasing lips width and lenght caused by decreasing I-Mc Namara Line distance on class II division 1 malocclusion treated Begg Fixed aplliance. However, the number of changes of I-Mc Namara distance was no significantly correlation with the number changes of lips width and lenght.